Access to Legal Information in india - Chander, Satish (DESIDOC Journal of Library & Information Technology, 2003)
The paper briefly describes the existing important legal information systems functioning in western countries and Australia. It also enumerates the efforts made by supreme court of india to organise legal information pertaining to decided cases.The paper also discusses COURTING, introduced by National Informatics Centre (NIC) in collaboration with supreme court of India.It provides information on the Apex Court to a wide range of users who are interested in legal developments and judicial decisions of the Supreme Court. http://dx.doi.org/10.14429/dbit.18.4.3404